Family Background Memoderasi Social Norms Terhadap Entrepreneurial Intention - Neng Sri Nuraeni; Disman Disman; Eeng Ahman; Kusnendi Kusnendi (Esensi: Jurnal Bisnis dan Manajemen, 2021)
The purpose of this research is to examines the role of family background in moderating the relationship between social norms and entrepreneurial intention. The method used in this research is the explanatory survey method. Testing of the conditional process model in this study uses path analysis based on OLS (Ordinary Least Square) regression and the bootstrap method uses statistical tools SPSS version 23 and PROCESS version 3.4 by Andrew F. Hayes, the 1st model. This test is performed to measure the direct effect and indirect effect, as well as the total effect of the effect of the independent variable on the dependent variable. The results of the study state that social norms have a positive and significant effect on entrepreneurial intention. Meanwhile, family background has no positive and significant effect on entrepreneurial intention. Family background effectively moderates the relationship between social norms and entrepreneurial intention.Cara Mengutip:Nuraeni, N. S., Disman., Ahman, E., & Kusnendi. (2021). Family Background Memoderasi Social Norms Terhadap Entrepreneurial Intention. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.20829.